Motivations for the practice of veganism and vegetarianism in a sample of adherents from the city of São Paulo - Hae so Lee, Carolina; Cabral, Ana Cristina Medeiros Moreira; Maia , Luana Bandeira (Seven Editora, 2023)
Introduction: Currently, it is observed that vegan and vegetarian diets have been much discussed in various media, attracting looks from those who seek to understand it as an awareness movement. In vegetarianism, most or all animal products are excluded, depending on the variations or subtypes. Veganism, in turn, encompasses dietary and social practices motivated by the non-exploitation or use of animals in all possible sectors. Today’s society increasingly demands the need to consider ecological and social issues in choices and decision-making. Objectives: To identify the reason for choosing to adhere to a vegan or vegetarian diet in a sample of practitioners from the city of São Paulo. Methods: Cross-sectional study with qualitative analysis of the results. An adaptation of the questionnaire "Public opinion survey on vegetarianism" of IBOPE Intelligence (2018) was elaborated with open and closed questions, which was applied through the Google forms platform to a sample of 22 participants, inhabitants of the city of São Paulo and adherents to vegan/vegetarian diets for at least one year. The questionnaire was disseminated through online social platforms. Results and discussion: The sample had the participation of 72.7% of individuals aged 18 to 30 years, most of them female (90.9%). The information collected states that the vegan/vegetarian diet is considered today as a ’lifestyle’, more than a diet, also associated with ’personal identity’. In addition, the ’strong feeling of empathy for animals and their causes’, ’awareness of the environmental impacts of the omnivorous diet’, ’improvement in quality of life or health’ and ’feeling of lightness or purity in the spiritual and/or mental and/or psychological sphere’ were the main motivating items for adherence to the vegan/vegetarian diet, respectively. Conclusion: The present study allowed a deeper understanding of the vegan/vegetarian diet in Brazil and the world, its origins, dilemmas and diverse interpretations. The movement is relatively new, not only as a form of food, but also as a lifestyle. DOI:https://doi.org/10.56238/alookdevelopv1-168